Valuing CTT : a 495 year old company competing in the 21st Century Postal Market : equity valuation : CTT – Correios de Portugal, SA - Teixeira, Joana Mendonça de Jesus de Assis (2016)
The goal of a thesis in the field of Firm Valuation are, firstly, to draw valid assumptions applicable to previously studied methods that best fit the valuation of a chosen company in order to find an accurate price for its stock. Upon making so, it is also expected a comparison between the results found and the ones published by a leading investment bank, also, of one’s choice. The differences as well as similarities between methodologies and values found shall be assessed, discussed and justified. The company chosen for the latter purposes is CTT, a 495 year old company facing the new landscape of the postal market: as traditional mail becomes obsolete, Express and Parcels as well as Financial Services are boosting industry’s revenues. An analysis to past performance seems to have prepared CTT for “a change in the game”, for the company continues to yield strong EBITDA margins motivated by the cost control efficiency aligned with network optimization. The proposed price target is 10.67€ which intentions to reflect the (i) electronic substitution effect, (ii) the Portuguese economic evolution and (iii) CTT’s own internal initiatives which aim to take advantage of the latter two. Moreover it is worth referring the free-float of 100%, which guarantees high levels of liquidity in the stock market, enabling share price to growth even further.